Model Fisik Kincir Air Sebagai Pembangkit Listrik - Akhiar Junaidi; Rinaldi Rinaldi; Andy Hendri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One type of renewable energy is a small-scale hydropower, or often referred to as micro or also called micro hydro power plant (MHP). Microhydro get energy from water flow that has a certain height difference and flow velocity. The energy generated by physical model waterwheel is a renewable energy can be measured by using a digital torque tester is connected to the axis windmill models. High rotation speed does not necessarily have a great energy because if given half the load will greatly affect the rotation speed. This research is to develop the technology, materials, mechanical components, electronic component and system design of energy resources, so as to have a strategic impact on the development of technology and can be applied in the community. Wheel rotation measurement using rpm tachometer generates value that affects the value of the energy generated from the windmill. The model used is Undershot wheel.Keyword : PLTMH, Torque Tester, Rpm, Undershot